Bilingual first language acquisition (BFLA) of Bangla and English : a case study - Parveen, Shapla (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The aim of this research was to provide a comprehensive view in understanding the phenomenon of 'bilingual first language acquisition' (BFLA) by exploring the simultaneous acquisition of Bangla and English of a child as his first two languages. The child received English input from his mother, and Bangla input from his father and maternal grandmother on a regular basis, thus, following the One-Parent-One-Language family policy. It is a longitudinal case study, exploring the nature of the child's language developmental patterns over a two year period, in a natural home environment, starting from eight months to two years and eight months of age. It followed the theoretical and methodological guidelines from both infant bilingual acquisition and child language acquisition perspectives. Since the input factor was taken as an important variable in this research, it also employed the 'social interactionist approach' as an attempt to interpret how the dual language input conditions had impact on the bilingual developmental patterns of the child in question. Besides, since it involved the simultaneous acquisition of two languages; hence, the rationale for using the “Separate System Hypothesis”. The study focused on some of the key areas of phonological, morpho-syntactic as well as language mixing. Data analysis revealed that the child was producing linguistic elements from both the languages and a gradual progress was visible. Although his Bangla phoneme development was more distinguishable than the English phonemes in the early phases, the English phonemes gradually became clearer and perceptible in the later phase of the study period. His 'stop' sounds particularly the aspirated stops in both the languages were distinct in onset positions; the English vowels and 'fricatives' which were absent in the Bangla sound system also developed gradually. He also picked up the rhotic feature from his mother's accent during his interaction with his mother. Data also revealed that the child's Bangla syntax was stronger in most of the stages of his syntactic development with more morpheme categories. The MLU chart demonstrated a steady increase in his morpho-syntactic development in both the languages with higher MLU score in Bangla. The environmental input conditions could have led to this effect in his language development. Since Bangla is morphologically richer with more inflections, there were also instances of this category in his utterances, especially in the last phase of the study period. There were also evidence of language mixing in both phonology and syntax, which could be related to the pragmatic situation of his language environment and the discourse strategies employed by his caregivers. In spite of the fact that language mixing elements were evident in the child's speech, traces of language differentiation also appeared to be evident. It appeared that the child was aware of the two languages that were exposed to him. This study attempted to initiate more interest on children's acquisition of not only Bangla and English as their first languages, but also other language pairs in dual language development, and append further to the literature of case studies in bilingual first language acquisition. The study may also have implications in the fields of child language education and early bilingual education itself.